SOLVING CORE MODEL AND CALCULATING SHAPLEY VALUE FOR THREE PEOPLE COOPERATIVE GAME USING BARYCENTRIC COORDINATE METHOD - Nrangwesti, Windi
Game theory is an interaction between more than two people with asumption that each person want to maximize the their outcome. There are two different types of game theory which are cooperative and non-cooperative game . The characteristic of the cooperative game is the existence of coalition in the game. The coalition help to determine the amount of payoff which is gained by the person in the game. Furthermore, this final project will discuss about the core model of cooperative game , determine the feasible set of the core using Barycentric coordinate method, and application of the Shapley value to find the average payoff to the player if the players are entered in completely random order.